Effect of firm specific factors and reinsurance on performance of Nepalese Insurance Companies - Wosti, Narayan; Pradhan, Sumit (The Lumbini Journal of Business and Economics, 2023)
This study examines the effect of firm specific factors and reinsurance on performance of Nepalese insurance companies. Return on assets (ROA) and return on equity (ROE) are the dependent variables. The selected independent variables are firm size, liquidity, assets tangibility, net claim ratio, net commission ratio and ratio of ceded reinsurance. The study is based on secondary data of 16 insurance companies with 124 observations for the period from 2013/14 to 2020/21. The data are collected from the annual reports of the selected insurance companies and annual report published by Rastriya Beema Samiti. The regression models are estimated to test the significance and effect of firm specific factors and reinsurance on performance of Nepalese insurance companies.